Designing a tissue-engineered tracheal scaffold for preclinical evaluation. (January 2018) - Best, Cameron A.; Pepper, Victoria K.; Ohst, Devan; Bodnyk, Kyle; Heuer, Eric; Onwuka, Ekene A.; King, Nakesha; Strouse, Robert; Grischkan, Jonathan; Breuer, Christopher K.; Johnson, Jed; Chiang, Tendy
Abstract: Objective: Recent efforts to tissue engineer long-segment tracheal grafts have been complicated by stenosis and malacia. It has been proposed that both the mechanical characteristics and cell seeding capacity of TETG scaffolds are integral to graft performance. Our aim was to design a tracheal construct that approximates the biomechanical properties of native sheep trachea and optimizes seeding with bone marrow derived mononuclear cells prior to preclinical evaluation in an ovine model. Methods: A solution of 8% polyethylene terephthalate (PET) and 3% polyurethane (PU) was prepared at a ratio of either 8:2 or 2:8 and electrospun onto a custom stainless steel mandrel designed to match the dimensional measurements of the juvenile sheep trachea. 3D-printed porous or solid polycarbonate C-shaped rings were embedded within the scaffolds during electrospinning. The scaffolds underwent compression testing in the anterior-posterior and lateral-medial axes and the biomechanical profiles compared to that of a juvenile ovine trachea. The most biomimetic constructs then underwent vacuum seeding with ovine bone marrow derived mononuclear cells. Fluorometric DNA assay was used to quantify scaffold seeding. Results: Both porous and solid rings approximated the biomechanics of the native ovine trachea, but the porous rings were most biomimetic. The load-displacement curve of scaffolds fabricated from a ratio of 2:8 PET:PU most closely mimicked that of native trachea in the anterior-posterior and medial-lateral axes. Solid C-ringed scaffolds had a greater cell seeding efficiency when compared to porous ringed scaffolds (Solid: 19 × 10 4 vs. Porous: 9.6 × 10 4 cells/mm 3, p = 0.0098). Conclusion: A long segment tracheal graft composed of 2:8 PET:PU with solid C-rings approximates the biomechanics of the native ovine trachea and demonstrates superior cell seeding capacity of the two prototypes tested. Further preclinical studies using this graft design in vivo would inform the rational design of an optimal TETG scaffold.